Law Enforcement Against Perpetrators of Child Exploitation Through Tiktok Social Media For Economic Gain - Simare Mare, Chandra P; July Esther; Debora (PT FORMOSA CENDEKIA GLOBAL, 2025)
The issue of child exploitation on social media, particularly TikTok, is getting worse. Without considering the detrimental effects, children are exploited for selfish purposes. The purpose of this study is to learn about legal actions taken by law enforcement against those who exploit children and initiatives to shield kids from being exploited on social media in line with the Child Protection Law. Using a normative juridical approach and a qualitative methodology, legal document analysis and literature review are employed. The study's findings demonstrate that, in spite of numerous regulations, the community's inconsistent knowledge of the law, a lack of agency cooperation, and a lack of funding continue to impede compliance.